Global environmental change and health: impacts, inequalities, and the health sector - McMichael, A J (BMJ Publishing Group Ltd., 2008)
Human pressures on the environment are damaging the world’s biophysical and ecological systems. A J McMichael and colleagues discuss the resulting unequal effects on health and set out strategies to help prevent and lessen the harm